Efektifitas Pembelajaran Kitab Akhlak Lil Banin Dalam Membentuk Akhlak Santri Pondok Pesantren Miftahul Jannah Karang Jaya - Suwita Dela; Masudi Masudi; Eka Yanuarti (El-Ghiroh : Jurnal Studi Keislaman, 2020)
Researcher Conducted research on Diniyah madrasah education which consisted of two classes for volume one and two consisting of 65 students and for volume three and four consisting of 32 students. In this study, the objectives are first to determine the effectiveness in the learning process of lilbanin morals, second to determine the effectiveness in shaping the morals of students in learning lil banin morals. descriptive qualitative research type. The conclusion is that the effectiveness of lil banin moral learning is quite good and has been very effective even though learning the lil banin book is a yellow book learning, so that the delivery of material is easy to understand by using attractive and appropriate methods such as exemplary methods, refraction, sorogan, wetonan, bandungan and memorization so that achieved in the formation of santri morals.